Alaska's Marine Minerals: A Case For Assessment And Evaluation - James C. Barker (International Marine Minerals Society, 1991)
Alaska's expansive continental shelf represents future opportunities for marine mineral development. Although today's metal prices and subsidized foreign mineral production continue to discourage industry investment in marine exploration worldwide, the longer term outlook is one of increasing costs on-shore with a dwindling land-base available on which to search for and extract minerals. Likely, the generations of the 21st century will increasingly recover their minerals from the sea-floor. Though largely unexplored, Alaska potentially represents a major port ion of the U.S. marine resources. Several factors demonstrate this. First, the Alaskan OCS is huge; 74% of the entire United States' continental shelf lies off of Alaska, and 54% of the U.S. coastline is Alaskan. Combined with the jurisdiction waters of the Soviet Far East, the Bering-Chukchi shelf is one of the world's largest tracts of shallow water. Second, Alaska is situated at the northwestern terminus of the mineral-rich American cordillera. From Chile to Alaska, major on-shore deposits of precious and base metals, ferroalloys, and industrial minerals are found in the tectonically disturbed belts of the cordillera. In 1988, the western U.S. cordilleran states produced 70% of this country's mineral output (excluding construction materials). Throughout the cordillera's entire 10,000 mile length, the rock units strike largely parallel to the coastline, but in Alaska they extend directly offshore and onto the continental shelf. Consequently, the mineral-rich terranes off of Alaska have a much more complex interaction with coastal and lit-